Densidade de estocagem para produção de acará-bandeira em viveiros escavados em policultivo com camarão-da-amazônia - Ribeiro, Felipe de Azevedo Silva; Jorge, Paulo Henrique; Fernandes, Joäo Batista Kochenborger [UNESP]; Sakomura, Nilva Kazue (My University, 2010)
The aim of this study was to evaluate the production of Freshwater Angelfish (Pterophyllum scalare) in different stocking densities in cages polycultured with Amazon River Prawn (Macrobrachium amazonicum). Four treatments were evaluated (1; 2; 3 and 4 fish.10 L-1) using two ponds and 24 experimental units. Water quality parameter reached adequate levels for the species. Production data were submitted to ANOVA. Fish produced in the lowest density showed higher values of final weight and standard length, and lower total biomass in comparison with the others treatments. Feed conversion rate, survival, batch uniformity and body factor were not significant different among treatments. The highest density tested produced more fish and gross yield than the others treatments. The density 20 fish.10L-1 is recommended to produce Freshwater Angelfish in cages polycultured with Amazon River Prawn.
Stocking density to produce freshwater angelfish polycultured in ponds with Amazon River Prawn
Keywords: Aquaculture; Aquarium fish; Macrobrachium amazonicum; Ornamental fish; Pterophyllum scalare